Top 10 Downloads from ACM's Digital Library. (Communications of the ACM, 2005)
The article presents information on top 10 downloads from the digital library of the May 2005 issue of the journal "Communications of the ACM." Some of the course title include, "Data Modeling"; "Introduction to the Java Programming Language"; "UML Fundamentals" et al.